2017
DOI: 10.1021/acs.chemmater.7b01847
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Zeolites in Aqueous Phase Reactions

Abstract: Strategies to understand and mitigate the corrosive interactions of zeolites in aqueous phase under reaction conditions have been explored using zeolite BEA as an example. The states of Si and Al atoms after chemical modification and during gradual degradation were followed by crosspolarization enhanced 29 Si MAS NMR and 27 Al MAS NMR as well as IR spectroscopy. The key to stabilizing a zeolite for aqueous phase catalysis is to reduce the pore concentration of water in the presence of reacting substrates. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(57 citation statements)
references
References 48 publications
1
53
0
Order By: Relevance
“…The successful synthesis of RuO 2 @MOF-808-P results in modulated CO/O adsorption behavior and a remarkable improvement in the CO oxidation performance on the RuO 2 surface at low temperatures. The PEGS method can be extended to other guests and nanoporous hosts with reasonable stability under desired synthesis conditions (Supplementary Figure 25 ) 24 , 64 . In theory, the PEGS approach is applicable to metals, oxides, hydroxides and sulfides 65 as long as their relevant Pourbaix diagrams indicate the feasibility of their formation.…”
Section: Discussionmentioning
confidence: 99%
“…The successful synthesis of RuO 2 @MOF-808-P results in modulated CO/O adsorption behavior and a remarkable improvement in the CO oxidation performance on the RuO 2 surface at low temperatures. The PEGS method can be extended to other guests and nanoporous hosts with reasonable stability under desired synthesis conditions (Supplementary Figure 25 ) 24 , 64 . In theory, the PEGS approach is applicable to metals, oxides, hydroxides and sulfides 65 as long as their relevant Pourbaix diagrams indicate the feasibility of their formation.…”
Section: Discussionmentioning
confidence: 99%
“…At a low Si/Al ratio (e.g., 15-50 for BEA), the concentration of Brønsted acid sites becomes decisive as it influences the amount of water in pores available for hydrolysis ( Figure 5C). [84,88] In the case of multicomponent systems (e.g., water solutions), water molecules are competing with less polar molecules for adsorption in pores. Zeolites with lower concentrations of acid sites tend to adsorb a smaller quantity of water from steam and therefore are more stable in comparison with aluminum-rich ones, while for liquid water conditions the trend is the opposite (increase in Si/Al results in decreased stability).…”
Section: Hot Liquid Watermentioning
confidence: 99%
“…A particular influence of the fluoride route is the significant reduction of the amount of silanol defects, resulting in more hydrophobic and hydrothermally stable materials in comparison to zeolites conventionally prepared in alkaline media. [10][11][12] More recently, it has also been reported that introduction of NaF during the synthesis of high-silica CHA zeolites results in additional (intracrystalline) microporosity, which can greatly enhance mass transport of reactants to active sites during catalysis. 13,14 Framework etching with HF or NH 4 HF 2 is another method to introduce additional porosity in zeolites.…”
Section: Introductionmentioning
confidence: 99%